OPTIMIZATION STRATEGY IN ENERGY SAVING OF CHILLER PLANT SYSTEMS - RAZMANI, RADHI (IRC, 2017)
Chiller water plant systems have been found to operate at a lower efficiency during part load conditions in tropical countries like Malaysia. The inefficient performance of the chillers results in an increase in the system energy consumption that ultimately affects the electrical demand of a particular building. This paper analyzes and identifies optimization strategies that provides the greatest impact on increasing the efficiency at part load conditions of specifically air-cooled chiller plant systems. The research focuses on the application of variable speed drives (VSD) on system components of a centralized centrifugal chiller compressor system at part load conditions where the system energy usage and coefficient of performance are compared to that of a conventional chiller system. A semi-empirical model of both the chiller plant system performance and the results obtained are compared to identify the effectiveness of the optimization strategy. A cooling load profile of a typical building is used to evaluate the potential energy savings following the increase in chiller COP and efficiency. It was found that the total annual energy consumed by the constant flowrate chiller and VSD integrated chiller is 20.71 GW and 14.75 GW respectively, hence a 28.7% reduction in energy usage is observed with the implementation of the optimization strategy. Based on the results of both the models, the integration of the VSD allows the COP of the chiller plant to increase. An increase in energy savings and reduction in emissions is seen when the speeds of the chilled water pump, compressor, and condenser pump are adjusted to meet current load conditions. The results of this study will be a benchmark for designers and engineers in an effort to further improve the performance of chiller plant systems.